Heminested reverse-transcriptase polymerase chain reaction (hnRT-PCR) as a tool for rabies virus detection in stored and decomposed samples - Araújo, Danielle B. [UNESP]; Langoni, Hélio [UNESP]; Almeida, Marilene F.; Megid, Jane [UNESP] (Springer Nature, 2008)
Background. The use of methods, both sensitive and specific, for rabies diagnosis are important tools for the control and prophylaxis of the disease. Reverse-Transcriptase Polymerase Chain Reaction (RT-PCR) has been used in rabies diagnosis with good results, even in decomposed materials. Additionally, molecular techniques have been used for epidemiological studies and to gain a better knowledge of viral epidemiology. Findings. The aim of this work was to evaluate the RT-PCR and hnRT-PCR for rabies virus detection in original tissues stored at -20°C for different periods considering their use for rabies virus detection in stored and decomposed samples. RT-PCR and hnRT-PCR were evaluated in 151 brain samples from different animal species, thawed and left at room temperature for 72 hours for decomposition. The RT-PCR and hnRT-PCR results were compared with previous results from Direct Fluorescent Antibody Test and Mouse Inoculation Test. From the 50 positive fresh samples, 26 (52%) were positive for RT-PCR and 45 (90%) for hnRT-PCR. From the 48 positive decomposed samples, 17 (34, 3%) were positive for RT-PCR and 36 (75%) for hnRT-PCR. No false-positives results were found in the negatives samples evaluated to the molecular techniques. Conclusion. These results show that the hnRT-PCR was more sensitive than RT-PCR, and both techniques presented lower sensibility in decomposed samples. The hnRT-PCR demonstrated efficacy in rabies virus detection in stored and decomposed materials suggesting it's application for rabies virus retrospective epidemiological studies. © 2008 Arajo et al; licensee BioMed Central Ltd.
Keywords: Animalia; Rabies virus